Validation and Update of the Lémann Index to Measure Cumulative Structural Bowel Damage in Crohn's Disease - Pariente, Benjamin; Torres, Joana; Burisch, Johan; Arebi, Naila; Barberio, Brigida; Duricova, Dana; Ellul, Pierre; Goldis, Adrian; Kaimakliotis, Ioannis; Katsanos, Konstantinos; Krznaric, Željko; McNamara, Deirdre; et al. (Gastroenterology, 2021)
BACKGROUND & AIMS: The Lémann Index is a tool measuring cumulative structural bowel damage in Crohn's disease (CD). We reported on its validation and updating. METHODS: This was an international, multicenter, prospective, cross-sectional observational study. At each center, 10 inclusions, stratified by CD duration and location, were planned. For each patient, the digestive tract was divided into 4 organs, upper tract, small bowel, colon/rectum, anus, and subsequently into segments, explored systematically by magnetic resonance imaging and by endoscopies in relation to disease location. For each segment, investigators retrieved information on previous surgical procedures, identified predefined strictures and penetrating lesions of maximal severity (grades 1-3) at each organ investigational method (gastroenterologist and radiologist for magnetic resonance imaging), provided segmental damage evaluation ranging from 0.0 to 10.0 (complete resection). Organ resection-free cumulative damage evaluation was then calculated from the sum of segmental damages. Then investigators provided a 0-10 global damage evaluation from the 4-organ standardized cumulative damage evaluations. Simple linear regressions of investigator damage evaluations on their corresponding Lémann Index were studied, as well as calibration plots. Finally, updated Lémann Index was derived through multiple linear mixed models applied to combined development and validation samples. RESULTS: In 15 centers, 134 patients were included. Correlation coefficients between investigator damage evaluations and Lémann Indexes were >0.80. When analyzing data in 272 patients from both samples and 27 centers, the unbiased correlation estimates were 0.89, 0,97, 0,94, 0.81, and 0.91 for the 4 organs and globally, and stable when applied to one sample or the other. CONCLUSIONS: The updated Lémann Index is a well-established index to assess cumulative bowel damage in CD that can be used in epidemiological studies and disease modification trials.
Keywords: Decision Support Techniques; Reproducibility of Results; Cross-Sectional Studies; stupeň závažnosti nemoci; metody pro podporu rozhodování; reprodukovatelnost výsledků; Intestines; Bowel Damage; Crohn’s Disease; gastrointestinální endoskopie; Europe; Tomography, X-Ray Computed; Predictive Value of Tests; Validation; Evropa; mužské pohlaví; prediktivní hodnota testů; Crohnova nemoc; průřezové studie; Adult; Prospective Studies; Colonoscopy; střeva; magnetická rezonanční tomografie; Magnetic Resonance Imaging; ženské pohlaví; City of New York; Endoscopy, Gastrointestinal; prospektivní studie; Humans; New York City; Crohn Disease; Lémann Index; dospělí; počítačová rentgenová tomografie; Female; Severity of Illness Index; lidé; Male; kolonoskopie